Irregular Dynamics of the Center of Mass of Droplets - Almeida, Alexandre B.; Giovambattista, Nicolas; Buldyrev, Sergey V.; Alencar, Adriano M. (Journal of Applied Nonlinear Dynamics, 2026)
The understanding of droplets is important to different applications, ranging from wetting to diagnosis of airways condition in the lung. In this work, we performed molecular dynamics and Monte Carlo simulations to solve the displacement of center of mass (CM) of droplets, in order to calculate the Hurst exponent in z-coordinate and in the xy-plane. Depending on the confinement condition, the CM motion, can be persistent, anti-persistent, Brownian or confined.